An Architecture for Agile Systems Engineering of Secure Commercial Off‐the‐Shelf Mobile Communications. Issue 1 (January 2017) - Gump, Jamieson; Mazzuchi, Thomas; Sarkani, Shahram
ABSTRACT: The federal government has long had a need for highly secure communications. The National Security Agency (NSA) is responsible for the wide range of technologies to secure these communications. They realized, recently, that the development times for government encryption technology was not keeping pace with the rapid evolution of commercial mobile technologies; together with a realization that commercial technologies exist to meet the requirements for the federal government. Specifically, NSA has published specifications on their website to operationalize these capabilities. Commercial Solutions for Classified (CSfC), the NSA term for commercial off‐the‐shelf (COTS) secure communications, coupled with published capability packages allows a developer to field a secure communications solution rapidly built entirely on COTS technology. The architecture, proposed in this paper, will address the rapidly evolving commercial mobile security market and will address fully leveraging commercial technologies to field the latest technologies in the shortest amount of time and at the lowest cost. With the NSA move to commercial technologies and the commercial market moving to enhanced security for "standard commercial users, " there is an emerging convergence of these two approaches. The initial work has revealed effective architectural constructs to support the wide range of emerging applications of this promising approach from NSA.